2023
DOI: 10.1002/cb.2130
|View full text |Cite
|
Sign up to set email alerts
|

The value created by the removal of cut lines: Evaluating the impact of finishing of industrial designs on purchase intention

Abstract: Color, material, and finish (CMF) are essential to the competitiveness of industrial products. However, in the existing research on CMF from the consumer behavior perspective, there is an insufficient focus on finish, compared with that on color and material. Research on finish is limited to technical methods, and there is a lack of discussion about its impact on consumer purchasing behavior. This study examines the effect of cars' exterior design finish on purchase intention in Japan. The research question is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Similarly, Sutisna and Handra (2022) and Hendriyati et al (2022) explained consumer behaviour as a motivation that leads towards the consumption process encompassed by the feelings and thoughts of the consumer and the actions taken during the time of purchase. Kato et al (2023), Kirby et al (2006), Apple (2020), andBaptista et al (2021) emphasized material, colour, and finish are essential for the competitiveness of industrial products. Locating the significant impact of cars' external finishing on the final purchase intention of a consumer, Kato et al (2023) suggested that industries change their mindset, especially those who believe less in the quality of product having either of the repercussions on the consumer's intentions towards the car purchase.…”
Section: Insight On the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Sutisna and Handra (2022) and Hendriyati et al (2022) explained consumer behaviour as a motivation that leads towards the consumption process encompassed by the feelings and thoughts of the consumer and the actions taken during the time of purchase. Kato et al (2023), Kirby et al (2006), Apple (2020), andBaptista et al (2021) emphasized material, colour, and finish are essential for the competitiveness of industrial products. Locating the significant impact of cars' external finishing on the final purchase intention of a consumer, Kato et al (2023) suggested that industries change their mindset, especially those who believe less in the quality of product having either of the repercussions on the consumer's intentions towards the car purchase.…”
Section: Insight On the Literaturementioning
confidence: 99%
“…Kato et al (2023), Kirby et al (2006), Apple (2020), andBaptista et al (2021) emphasized material, colour, and finish are essential for the competitiveness of industrial products. Locating the significant impact of cars' external finishing on the final purchase intention of a consumer, Kato et al (2023) suggested that industries change their mindset, especially those who believe less in the quality of product having either of the repercussions on the consumer's intentions towards the car purchase.…”
Section: Insight On the Literaturementioning
confidence: 99%
See 1 more Smart Citation